Remarkable Breakthrough: Unleashing the Power of Paclitaxel and Carboplatin in Defeating Squamous Cell Carcinoma (SCC) of the Lungs - A Compelling Case Report - Novita Andayani; Murtaza Murtaza; Rina Marlena; Syarifah Fera Muhawan (Indonesian Society of Respirology (ISR), 2023)
Background: This case report focuses on the evaluation of treatment efficacy in a 64-year-old male patient diagnosed with stage IVA lung squamous cell carcinoma (SCC) in the right upper lobe. The patient underwent chemotherapy using paclitaxel and carboplatin, administered in measured doses over six cycles. Close monitoring of patients was conducted throughout the treatment period, taking into account their clinical condition. Case: The patient underwent a computerized tomography (CT) examination before starting treatment, followed by a comparison in the third month of treatment. Encouragingly, significant clinical improvement was observed with respect to the initial complaint. The patient achieved an excellent response, the tumor appearance disappeared and the previous size was assessed by Partial Response (PR) based on RECIST criteria. Discussions: The administration of paclitaxel and carboplatin in patients with SCC gave positive results. Metered doses and scheduled administration allow for effective disease management, leading to substantial clinical improvement. The case studies highlight the potential of this treatment regimen in treating SCC, emphasizing the importance of close monitoring during therapy. Conclusion: This case report underscores the promising results obtained with paclitaxel and carboplatin in the treatment of lung SCC. The patient's notable response, marked by clinical improvement and achieving a partial response based on RECIST criteria, exemplifies the potential of this therapeutic approach. Further investigations and clinical trials are warranted to explore the broader applicability and efficacy of this regimen.